2012
DOI: 10.1186/1757-7241-20-54
|View full text |Cite
|
Sign up to set email alerts
|

Acute lung injury and the acute respiratory distress syndrome in the injured patient

Abstract: Acute lung injury and acute respiratory distress syndrome are clinical entities of multi-factorial origin frequently seen in traumatically injured patients requiring intensive care. We performed an unsystematic search using PubMed and the Cochrane Database of Systematic Reviews up to January 2012. The purpose of this article is to review recent evidence for the pathophysiology and the management of acute lung injury/acute respiratory distress syndrome in the critically injured patient. Lung protective ventilat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
105
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(108 citation statements)
references
References 75 publications
1
105
0
2
Order By: Relevance
“…The present therapeutic approaches for ALI include supportive care, ventilator support, pharmacological treatments and mesenchymal stem cells (MSCs) [2, 7-9]. ALI can develop into more severe acute respiratory distress syndrome (ARDS) or multiple organ dysfunction syndrome (MODS), and the incidence and mortality of ALI remains high around the world [7, 10]. Therefore, developing novel therapies to treat ALI and improve the clinical outcomes is urgently necessary.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present therapeutic approaches for ALI include supportive care, ventilator support, pharmacological treatments and mesenchymal stem cells (MSCs) [2, 7-9]. ALI can develop into more severe acute respiratory distress syndrome (ARDS) or multiple organ dysfunction syndrome (MODS), and the incidence and mortality of ALI remains high around the world [7, 10]. Therefore, developing novel therapies to treat ALI and improve the clinical outcomes is urgently necessary.…”
Section: Introductionmentioning
confidence: 99%
“…Lipopolysaccharide (LPS) is a key component of the cell wall of gram-negative bacteria that can induce pulmonary and systemic infection [3, 10, 11]. LPS participates in initiating the inflammatory response by binding to its receptors.…”
Section: Introductionmentioning
confidence: 99%
“…According to Hudson et al, ARDS develops in 25% of patients with multiple injuries [11]. Bakowitz and all define trauma as the main predisposing condition in 7% cases of ARDS [2]. Recent USA multicenter randomized trials show the incidence of trauma-related ARDS to be 6.5% of traumatically injured patients [16,19].…”
Section: Discussionmentioning
confidence: 99%
“…We believe that TBI evokes pulmonary complications causing hypoxia in normoventilated patients. (18,19) The possible beneficial effect of early out-of-hospital intubation to secure the airway and to prevent hypoxia and aspiration has been questioned. Many studies have shown that a pre-hospital ETI in patients with TBI is associated with increased mortality.…”
Section: Discussionmentioning
confidence: 99%